2019
DOI: 10.1021/acsinfecdis.8b00253
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aspects of the Coadministration of Sterol 14α-Demethylase Inhibitor VFV and Benznidazole in Experimental Mouse Models of Chagas Disease Caused by the Drug-Resistant Strain of Trypanosoma cruzi

Abstract: Up to now, no vaccines are available for Chagas disease, and the current therapy is largely unsatisfactory. Novel imidazolebased scaffolds of protozoan sterol 14α-demethylase (CYP51) inhibitors have demonstrated potent antiparasitic activity with no acute toxicity. Presently our aim was to investigate the effectiveness of the experimental 14α-demethylase inhibitor VFV in the mouse models of Trypanosoma cruzi infection using a naturally drug-resistant Colombiana strain, under monotherapy and in association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Considering all the results obtained in vivo , these monotherapy protocols conducted with both 5-nitroindazole derivatives did not lead to better effectiveness than BZ; however, the co-administration schemes showed superior anti-parasitic profile than the reference drug. Recently, other pre-clinical studies have revealed important findings of trypanocidal effectiveness in vivo by co-administering different compounds with the reference drug BZ (Guedes-da-Silva et al ., 2019; Simões-Silva et al ., 2019). The implementation of combined therapies is an alternative actually considered for the treatment of CD (Sales Junior et al ., 2017; Ribeiro et al ., 2020), and already in clinical use for combating many illnesses, including those triggered by parasitic infections, such as malaria (WHO, 2015) and sleeping sickness (WHO, 2019), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all the results obtained in vivo , these monotherapy protocols conducted with both 5-nitroindazole derivatives did not lead to better effectiveness than BZ; however, the co-administration schemes showed superior anti-parasitic profile than the reference drug. Recently, other pre-clinical studies have revealed important findings of trypanocidal effectiveness in vivo by co-administering different compounds with the reference drug BZ (Guedes-da-Silva et al ., 2019; Simões-Silva et al ., 2019). The implementation of combined therapies is an alternative actually considered for the treatment of CD (Sales Junior et al ., 2017; Ribeiro et al ., 2020), and already in clinical use for combating many illnesses, including those triggered by parasitic infections, such as malaria (WHO, 2015) and sleeping sickness (WHO, 2019), among others.…”
Section: Discussionmentioning
confidence: 99%
“…The use of suboptimal doses or treatment length of BNZ in association with CYP51 inhibitors may maintain or increase the effectiveness of treatment by the synergistic or additive effect of compounds with different mechanisms of action or cellular targets. 56 , 118 , 119 , 150 , 155–157 , 176–180 Similarly, allopurinol combined with low dose of BNZ had a positive interaction in T. cruzi infection outcome. 172 , 181 Sequential treatment with allopurinol and BNZ was able to reduce parasitemia and attenuate tissue damage in infected mice.…”
Section: Drug Combination Therapymentioning
confidence: 93%
“… [ 116 , 117 ] [ 118 ] VFV VFV was more potent than VNI in reducing parasitemia and presented effects on mortality protection. [ 60 , 119 ] VNI VNI presented promising anti- T. cruzi activity in vitro and in vivo. The drug promoted reduction of parasitemia in mice infected by different strains.…”
Section: New Drug Candidates For Chagas Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Significantly diminished the parasitic load in blood and the mortality rateProvidello et al (2018)Ascorbic Acid (Genitourinary Agent)Benznidazole (Antiprotozoal)Swiss miceReduction in parasitemia, in cardiac parasitism and inflammation, and prevention of the hepatic damage.Scarim et al, 2018b, Scarim et al, 2018aHydroxymethylnitrofurazone (a nitrofurazone prodrug)Benznidazole (Antiprotozoal)Balb/c miceAmastigote nests were not found in heart, skeletal muscle, liver, kidney, colon, spleen and brain. The histopathological analysis showed fewer tissue lesions and parasite infiltratesTorrico F et al (2018)E1224 (a water-soluble ravuconazole prodrug)HumanE1224 displayed a transient, suppressive effect on parasite clearance, whereas benznidazole showed early and sustained efficacy until 12 months of follow-up.Guedes-da-Silva et al (2019)Sterol 14α-Demethylase (Inhibitor VFV)Benznidazole (Antiprotozoal)Swiss Webster miceparasitemia suppression and 100% animal survival Coadministration of Bz + VFV (resulted in 106-fold lower blood parasitism as compared to the monotherapy of Bz)De Araújo et al (2019)Imidazole Derivatives and Benznidazole (Antiprotozoal)MRC -5 cells and Primary cardiac cellsPotent and selective activity against T. cruzi Rial et al, 2019Allopurinol (Antigout) and Benznidazole (Antiprotozoal)C57BL/6J and C3H/HeN miceabsence of electrical abnormalities, significant reductions in antibody titres and parasitic loadsMazzeti et al, 2019Allopurinol combined with benzinidazole (Antiprotozoal) or Nifurtimox (Antiprotozoal)Mammalian cell, Swiss miceThe interactions were synergic. Administration of the drugs in combination increased the cure rate.Rocha et al (2019)Levamisole (anthelminthic)Benznidazole (Antiprotozoal)Swiss Webster miceIn vivo: The association partially reduced parasitemia and did not increased animal survivalND* not determined.…”
Section: Drug Associationmentioning
confidence: 96%